2022
DOI: 10.3390/ijerph19031608
|View full text |Cite
|
Sign up to set email alerts
|

Picturing Mental Health on Instagram: Insights from a Quantitative Study Using Different Content Formats

Abstract: Background: COVID-19 has changed individual lives to the core. Through national curfews and social distancing, individuals’ social lives changed and led to increased levels of stress and mental health problems. As another consequence, communication, especially among young people, has shifted to social networking sites, where particularly young adults sought help for their mental health problems. In recent years, Instagram has received recognition for its health-enhancing potentials. On this social networking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Studies have also shown that postings on social media lessen the stigma attached to mental health problems [ 5 , 6 ]. While the accompanying content may include true elements and details that define the topic, it may also include modified, incorrect, or irrelevant information that alters how users perceive information and the behaviors and beliefs that go along with it [ 7 , 8 ]. Thus, it is important to understand the accuracy and dependability of the information available on these platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that postings on social media lessen the stigma attached to mental health problems [ 5 , 6 ]. While the accompanying content may include true elements and details that define the topic, it may also include modified, incorrect, or irrelevant information that alters how users perceive information and the behaviors and beliefs that go along with it [ 7 , 8 ]. Thus, it is important to understand the accuracy and dependability of the information available on these platforms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, social media networks, especially Facebook, are now commonly used in medical research, specifically for cross-sectional design, and many studies have demonstrated its usefulness for quickly recruiting a large sample at the lowest cost [ 92 , 93 , 94 ]. Concerning other social media, although they are a little more recent than Facebook, their use is becoming more and more democratized in new studies, especially Instagram [ 95 , 96 ] and WhatsApp [ 97 , 98 ]. At the same time, we required that the respondents should be at least 18 years old to participate and asked for confirmation from each respondent.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also uncovered that social media messages can help to reduce mental health issues and the stigmatization associated therewith. [6] On social media like Instagram, there are multiple types of peer support for mental health, especially for people who are having hard times during the COVID-19 pandemic. Four forms of support can be distinguished: informational support, esteem support, emotional support, and network support.…”
Section: The Positive Impact Of Instagram During the Epidemicmentioning
confidence: 99%
“…At this point, the role of the influencer comes into play again, according to the study, …influencers thus started to thematize their personal mental health struggles, utilizing the diverse and varied presentation modes available on Instagram, which can increase both the visibility and relevance of the mental health discussion on social media. [6] Influencers informally affect the attitudes and opinions of their followers by posting mental health-related things that make their followers become aware of such issues. In the case of spreading messages, influencers and celebrities have similar functions because both of them are deemed credible and reliable by the public crowd, therefore anything they say or do greatly affects what the public crowd says or does.…”
Section: The Positive Impact Of Instagram During the Epidemicmentioning
confidence: 99%